Sources of negative differential resistance in electric nanotransport - Bâldea, Ioan; Köppel, Horst (Physical review. B, Condensed matter and materials physics, 2010)
A negative differential resistance (NDR) in nanotransport is often ascribed to electron correlations. We present a simple example revealing that finite electrode bandwidths and energy-dependent electrode density of states can cause a significant NDR, which may occur even in uncorrelated systems. So, special care is needed in assessing the role of electron correlations in the NDR.